Quality management in educational inspection services: adaptation to the EFQM excellence model - Hontañón Talledo, Alberto José (Avances en Supervisión Educativa, 2014)
The main purpose of this project work is to facilitate reflection on the incorporation of rigurous data gathering oriented to the decision making in order to improve the procedure carried out by the Educational Inspection Services, its operation and its results. By my understanding, due to their direct connection with the improvement in teaching practice, this improvement will thereupon result in significant benefits to education, the educational system and society itself. Throughout the project work, an approach to quality management is applied to improve the impact of the actions carried out by the Educational Inspection Services and a practical proposal, which sets out to encourage reflection in order to bent on change, is achieved together with a continuous improvement in the school supervision services themselves.
Keywords: education quality; assessment; educational inspection; continuous improvement; organization; quality management system; school supervision